La nonna canadese 2.0: Global Migrant or Marginal Player? - Colalillo, Giuliana (Italian Canadiana)

(untitled) (Iter Press, 2023)
Until the late 1970s, migration research seemed to assume that most migrants were male. It obscured the fact that women, too, were “on the move” and simply relegated female migrants as accessories to men. Today, the global dimensions of female migration are indisputable. Current research on the feminization of migration gives a face and voice to women, largely from developing countries, who have become key economic contributors to both the sending and receiving societies. It also brings into focus the paucity of research about the role and importance of Italian-Canadian immigrant women with respect to the success of many Italian immigrant families who arrived in the post–Second World War Italian diaspora. Within the growing research on female migration, this paper reviews the stereotypic representation of la nonna canadese in popular culture, Italian-Canadian literature, and the social sciences. Through the Nonna Canadese 2.0 Project, which involves one-on-one interviews with women who arrived in Canada in the 1950s and 1960s, this paper offers an updated perspective of the Italian-Canadian immigrant woman, one which allows her to take pride of place alongside her male counterpart.